2017
DOI: 10.1501/vetfak_0000002817
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the seroprevalence of BoHV-1 and CpHV-1 infections using gB/gE ELISA combination and VNT in selected goat flocks

Abstract: Summary:In this study, we have investigated the seroprevalence of alphaherpesvirus (BoHV-1 and CpHV-1) infections in selected goat flocks using glycoprotein B (gB)/glycoprotein E (gE) ELISA combination and virus neutralisation test (VNT). For this purpose, we collected blood serum samples of 546 Saanen goats from Bolu province and tested them by ELISA and VNT. Using ELISA, 32.05% (175/546) of the samples were found to be gB(+)/gE(-) for CpHV-1, whereas only 0.73% (4/546) of the samples were noted to be gB(+)/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…This study has already confirmed this claim, and also indicated that BoHV-1 might have caused mild infection in goats under variable conditions. Molecular studies on BoHV-1 in goats are scarce, and the majority of the performed studies have been based on serological techniques in Turkey (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019). Generally, seropositivity rates in goats to BoHV-1 have been reported to be between zero and 23% (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has already confirmed this claim, and also indicated that BoHV-1 might have caused mild infection in goats under variable conditions. Molecular studies on BoHV-1 in goats are scarce, and the majority of the performed studies have been based on serological techniques in Turkey (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019). Generally, seropositivity rates in goats to BoHV-1 have been reported to be between zero and 23% (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies on BoHV-1 in goats are scarce, and the majority of the performed studies have been based on serological techniques in Turkey (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019). Generally, seropositivity rates in goats to BoHV-1 have been reported to be between zero and 23% (Yesilbag et al, 2003;Yesilbag and Güngör, 2009;Ataseven et al, 2010;Baydın and Bilge-Dagalp, 2017;Gür et al, 2019). BoHV-1 serological studies in goats have been rarely performed, but two of them (Yesilbag et al, 2003;Yesilbag and Güngör, 2009) have reported 5.5 and 38.2% positivity in 2003.…”
Section: Discussionmentioning
confidence: 99%